PENGARUH PERSEPSI SISWA TENTANG KOMPETENSI PEDAGOGIK GURU DAN MINAT BELAJAR TERHADAP PRESTASI BELAJAR EKONOMI SISWA KELAS X SMA PGRI PEKANBARU - Ruth Trisnawati Malau; Gimin Gimin; Suarman Suarman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to know the influence of perceptions of students of pedagogic teacher competence and interest in learning achievement against learning economics students class X SMA PGRI Pekanbaru. The population in this research is the whole grade X SMA PGRI Soweto totalling 66 students of class X 1 IPA IPA, X 2, and X 1 IPS. This study uses census where all the population in the sample that is as much as 66 students. The data collected by using question form about the competence of teachers and pedagogic interest study with distributed to respondents as well as asking for a list of class X students economic value to the learning achievements of students. Data analysis using multiple linear regression analysis. In descriptive, perceptions of students of pedagogic competence teachers included on the category either (57.8%), interest in learning including on categories being (63.7%), including learning and achievement in the medium category (48.5%). Based on the results of the research of the influence of perceptions of students of pedagogic competence of teachers and learning interest in contributing to the effect on student learning achievement of 49.9% with regression equation Y = 46,444 + 0, 487X1 + 0, 948X2.Key Words: Competency pedagogy Teacher, Learning Interest and Learning Achievement